1992
DOI: 10.1177/019459989210600125
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Tympanostomy Otorrhea: A Randomized Clinical Trial of Topical Prophylaxis

Abstract: Myringotomy with the insertion of tympanostomy tubes has become the most frequently performed otolaryngologic procedure, and otorrhea is the most common post-tympanostomy complication. Many otolaryngologists routinely use prophylactic topical antibiotic solutions when performing tympanostomy tube placement. Relatively little has been written regarding early post-tympanostomy otorrhea and scarcely any examining the efficacy of such prophylaxis. The current study is a randomized clinical trial to critically eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 13 publications
1
39
1
4
Order By: Relevance
“…The rate of otorrhea in the control group of our study was 39.39%, higher than observed in the control group of other prospective trials, 10-30% [5][6][7][8][9][10][11][12][13]. Part of the explanation for this difference was that we analyzed the patient as a whole instead of ''per-ear''.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The rate of otorrhea in the control group of our study was 39.39%, higher than observed in the control group of other prospective trials, 10-30% [5][6][7][8][9][10][11][12][13]. Part of the explanation for this difference was that we analyzed the patient as a whole instead of ''per-ear''.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, some patients are unable to attend daycare/school settings with otorrhea, affecting quality of life. Several prospective studies using ototopical agents have shown a reduction in postoperative otorrhea [5][6][7][8][9][10][11][12][13][14]. In a meta-analysis of five Decrease in incidence of otorrhea with ciprofloxacin/dexamethasone drops prospective studies, ototopical antibiotics or antibiotic/steroid combinations administered perioperatively resulted in a reduction of post-operative otorrhea with the greatest benefit in patients with infection or purulent effusion at the time of surgery [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A distinction should be made between early otorrhea, which appears within 2-4 weeks after the operation, and delayed otorrhea, which occurs several months postoperatively [40]. The prevalence of early otorrhea ranges from 10 to 20% [4,5,19,22,26,36,57,65,66,81], whereas delayed otorrhea seems to be more frequent, occurring in 26% of cases [36]. Other studies have reported even higher rates of otorrhea, up to 50% of cases within a 3-year observation period [41,42] and even 83% in a study on children up to 36 months old at the time of insertion.…”
Section: Otorrheamentioning
confidence: 99%
“…The routine perioperative prophylactic use of local antibiotic ear drops flies in the face of evidence-based [19,66,81] A related meta-analysis found an 85% reduction of otorrhea when perioperative antibiotic drops were used [21], but the low incidence of this complication and the heterogeneity of the published studies prevented the authors from drawing a final conclusion; they therefore recommended the judicious use of these agents, with emphasis on those cases at higher risk of otorrhea, namely those with mucoid or purulent effusion. In terms of preventing biofilm formation, emphasis has been placed on the effect of a surface treatment of fluoroplastic grommets.…”
Section: Otorrheamentioning
confidence: 99%